Puccini's Turandot - Puccini, Giacomo; Fisher, Burton D. (Opera classics library, 2002)
A comprehensive guide to Puccini's TURANDOT, featuring insightful and in depth Commentary and Analysis, a complete, newly translated Libretto with Italian/English side-by side, and over 20 music highlight examples.
Keywords: Puccini, Giacomo, : 1858-1924 : Turandot; Operas : Librettos